20 MHz high frequency ultrasound assessment of scleral and intraocular conjunctival squamous cell carcinoma. Issue 6 (1st June 2002) - Char, D H; Kundert, G; Bove, R; Crawford, J B
Abstract : Aim: To assess in a prospective manner, high frequency ultrasound diagnosis of deep invasion by conjunctival squamous cell carcinoma. Methods: Prospective, non-randomised case series comparing 20 MHz high frequency ultrasonographic and clinicopathological data. Results: 20 MHz high frequency ultrasound delineated the degree of deep involvement of this tumour into the sclera, globe, and orbit. The results of ultrasonography correlated with the clinicopathological results. Conclusions: High frequency ultrasound is a useful diagnostic adjunctive test in patients with possible deep involvement by a conjunctival squamous cell carcinoma.